Evaluating the Predictive Value of the Dose-volume Parameters and Vascular Endothelial Growth Factor Expression on Rectal Toxicity in Prostate Cancer Patients - Marziyeh Mirzaeiyan; Hossein Khanahmad; Simin Hemati; Mahnaz Etehadtavakol; Zahra Sharifonnasabi; Parvaneh Shokrani (Journal of Medical Physics)
Background: The response to radiation varies widely among people. Despite recent advances to conform the dose distribution to the tumor volume, it is still impossible to perform radiotherapy based on the biological characteristics of each individual. In this case, identifying a biomarker can be a step toward personalizing treatment. This research was carried out to evaluate the predictive value of dose-volume parameters and vascular endothelial growth factor (VEGF) expression on rectal proctitis toxicity in prostate cancer patients. Materials and Methods: Eighteen patients with prostate cancer who underwent helical tomotherapy were included in the study. VEGF serum level before and after treatment was obtained. Furthermore, dosimetric parameters, including rectal volume, maximum dose, V50, V60, V65, V70, and V75 were extracted. Spearman’s correlation coefficient of VEGF-related and dosimetric parameters with the grade ≥1 rectal proctitis was calculated. Results: In the rectal toxicity group, the mean value of VEGF increased significantly after treatment compared to before (P = 0.008). Despite lower values of pre- and post-treatment VEGF in the toxicity group, this difference was not statistically significant (P > 0.05). Among the dosimetric parameters, only V65 had a significantly higher value in the toxicity group (P = 0.033). The highest correlation coefficients were obtained for pretreatment VEGF values and V65 (−0.446 and 0.450). Conclusion: The results of the study confirm the correlation of VEGF expression with the pathobiology process of rectal radiation proctitis. However, the pathobiology process of radiation proctitis is complicated. More research is needed to prove the involvement of VEGF expression in the early detection of proctitis.